Thank you to our 2022 reviewers - Shah, Ankoor S.; Savar, Aaron M. (Digital Journal of Ophthalmology, 2023)
The editors of the Digital Journal of Ophthalmology thank our expert peer reviewers for 2022. All of these individuals have volunteered their time to contribute to our goal of providing a high-quality free-access ophthalmic journal.